Assessment of color preference, purchase intention and sexual attractiveness of lipstick colors under multiple lighting conditions - Tian, Baolin; Gong, Hanwen; Chen, Zhiyu; Yu, Xuan; Pointer, Michael R.; Yu, Jie; Yu, Feng; Liu, Qiang (Frontiers in Neuroscience, 2023)
Lipstick is one of the most commonly used cosmetics, which is closely associated with female attractiveness and influences people's perception and behaviour. This study aimed to investigate the impact of light sources, lipstick colours, as well as gender on the subjective assessment of lipstick colour products from the prospective of colour preference, purchase intention and sexual attractiveness. The correlation between colour preference evaluations when applying lipstick on lips and on forearms was also explored. Sixty participants completed their visual assessment of 15 lipsticks worn by 3 models under 5 light sources, with uniformly sampled correlated colour temperature (CCT) values ranging from 2500 K to 6500 K. The results indicated that the light source significantly influenced colour preference and purchase intention, while lipstick colour significantly impacted on sexual attractiveness. The interactions between gender and other factors were also observed and are discussed. Compared to men, women were found to be more sensitive to different light sources and hold different attitudes towards different lipstick colours under different CCTs. Interestingly, no significant correlation was found between lipstick colour preference ratings on the lips and forearm, which conflicted with the commonly recognized way of lipstick colour selection. These findings should contribute to a deeper understanding of the consumer attitude towards lipstick colours and provide a useful reference for lighting design in situations where cosmetics are specified, manufactured, retailed and generally used, both professionally and in the home.